Poliovirus Unlinks TIA1 Aggregation and mRNA Stress Granule Formation - White, James P. (American Society for Microbiology, 2011)
In response to environmental stress and viral infection, mammalian cells form foci containing translationally silenced mRNPs termed stress granules (SGs). As aggregates of stalled initiation complexes, SGs are defined by the presence of translation initiation machinery in addition to mRNA binding proteins. Here, we report that cells infected with poliovirus (PV) can form SGs early that contain T-cell-restricted intracellular antigen 1 (TIA1), translation initiation factors, RNA binding proteins, and mRNA. However, this response is blocked as infection progresses, and a type of pseudo-stress granule remains at late times postinfection and contains TIA but lacks translation initiation factors, mRNA binding proteins, and most polyadenylated mRNA. This result was observed using multiple stressors, including viral infection, oxidative stress, heat shock, and endoplasmic reticulum stress. Multiple proteins required for efficient viral internal ribosome entry site-dependent translation are localized to SGs under stress conditions, providing a potential rationale for the evolution and maintenance of the SG inhibition phenotype. Further, the expression of a noncleavable form of the RasGAP-SH3 domain binding protein in PV-infected cells enables SGs whose constituents are consistent with the presence of stalled 48S translation preinitiation complexes to persist throughout infection. These results indicate that in poliovirus-infected cells, the functions of TIA self-aggregation and aggregation of stalled translation initiation complexes into stress granules are severed, leading to novel foci that contain TIA1 but lack other stress granule-defining components.